Assessment of supplementary food in Muktagacha pilot nutrition initiative of BRAC - Khatun, Masuma; Hyder, SM Ziauddin (BRAC Research and Evaluation Division (RED), 2019)
Food supplementation refers to providing additional food to the nutritional deprived population in addition to their regular diet to reduce or meet the gap between intake and requirement in order to improve their nutritional status. Since 1993 BRAC, through its Women's Health and Development Program (W1IDP), has been operating a pilot Nutrition Initiative in 158 villages of Muktagacha thana. The initiative used supplementary food as the vehicle to communicating nutritional messages to the community in addition to providing nutritional supplements to the target beneficiaries. This study was carried out to determine the nutritional quality and the cost of the supplemental foods as wen as the actual additional calorie consumption of the recipients from the food supplementation project. Nutrient analysis of the foods was performed at the Institute of Nutrition and Food Science (ThTFS), Dhaka University on 12 packets of supplemental foods which were randomly selected. It was revealed from the cost calculation that the cost per packet of adult and child food was Tk. 7.50 and 4.30 respectively. It was estimated that supplementary food, if taken completely, could provide energy equivalent to 752 kcal to a mother and 212 Kcal to a child under two years of age. However, mothers consumed around 75% of the food which provided 564 Kcallday. It was obsetved that the food was shared mostly with young children and husbands. In-depth interview ~ith mothers also suggest that they usually skip breakfast if the food is given in the morning. The children liked the food because of the taste and unless the child was sick or had some food before coming to the center, he ate the food completely (212 Kcal/day). Although the main purpose of the project was to provide nutrition education, it was observed that the activities at the feeding center was limited to food distribution and had very little to do with communication of nutritional messages. Therefore in the conclusion it was recommended that the service providers should be trained to communicate nutritional messages effectively as a part of understanding the goal of the initiative.